REAL TIME ONLINE EXAM PROCTORING SYSTEM IN HIGHER EDUCATION USING WEBRTC TECHNOLOGY - Maoeretz Engel, Mychael; Agustinus, Jeems Terri (Jurnal Teknik Informatika (Jutif), 2023)
The low level of trust in online exam results from students is a major problem because it is difficult to monitor whether test takers are taking the exam honestly according to their own abilities. Even though it has been assisted by the presence of video conferencing applications such as Zoom, Google Meet, Cisco Webex and similar applications, online exam proctoring is still unable to run effectively. Cheating in online exams, such as using dual monitors, is very possible for exam participants. Therefore, as a future preventive measure in the online exam process, a system is needed that can accommodate this concern. This research will create an online exam supervision system with WebRTC technology which has features to accommodate real-time supervision. The System Development Life Cycle method will be used in software development with 5 main stages, namely Requirement Analysis, Design, Development, Testing, and Maintenance. Implementation of the system was carried out during the online examination process for a class at one of the universities in Surabaya. Finally, the test results show that features such as: Live Proctoring get a score of 4.5; Attention Alert gets a score of 5; Exam Lock scored 4.5; Live Alert scored 4.5; and Tab & Window Detection got a score of 4; shows that this system has succeeded in providing a solution in online exam proctoring needs.